2006
DOI: 10.1590/s0037-86822006000300008
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de dermatófitos em amostras de unhas, pés e mãos coletadas de estudantes universitários

Abstract: RESUMOEste trabalho teve como objetivo, avaliar a presença de dermatófitos, especificamente em unhas, pés e mãos de estudantes universitários com e sem lesões sugestivas de dermatofitose. Foram coletadas 280 amostras dessas regiões, das quais 31 (11,1%) apresentaram positividade apenas pelo exame direto, e 20 (7,1%) tiveram, além do exame direto positivo, crescimento de dermatófito, mediante cultivo da amostra biológica. T. rubrum foi o dermatófito isolado com maior freqüência (80%), seguido por T. mentagrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…These cultures were interpreted as proof of the diagnostic hypothesis of mycosis. Verification of 47.8% of positive cultures is in agreement with the range of positivity that has been reported in the literature for these types of mycoses, which vary between 20.8% and 60%, when culture is considered a diagnostic criterion 40,50 . Several causes have been indicated to justify the low rate of fungi recovery in culture media, as registered in this study.…”
Section: Resultssupporting
confidence: 87%
“…These cultures were interpreted as proof of the diagnostic hypothesis of mycosis. Verification of 47.8% of positive cultures is in agreement with the range of positivity that has been reported in the literature for these types of mycoses, which vary between 20.8% and 60%, when culture is considered a diagnostic criterion 40,50 . Several causes have been indicated to justify the low rate of fungi recovery in culture media, as registered in this study.…”
Section: Resultssupporting
confidence: 87%
“…A total of 20 clinical isolates from nails and skin (four of T. rubrum and 16 of T. mentagrophytes) maintained in Sabouraud dextrose agar, at room temperature, until tested were included in this study 22 . Candida parapsilosis ATCC 22019 was the reference strain.…”
Section: Methodsmentioning
confidence: 99%
“…3 In Brazil, surveys by Siqueira et al (2006) and Brilhante et al (2000) 5 showed that the prevalence of dermatophytoses among cutaneous lesions ranges from 18.2 to 23.2%. 4,5 …”
Section: Introductionmentioning
confidence: 99%